Investigating the Interplay of Academic Stress, Anxiety, and Sleep Disturbances in College Students - Rianti, Nuras; Kholidin, Farid Imam; Yandri, Hengki (Buletin Konseling Inovatif, 2024)
Poor sleep quality negatively affects students' cognitive abilities. Meanwhile, improperly managed academic stress and anxiety exacerbates sleep disorders, potentially impeding academic performance. This study aimed to examine the relationship between academic stress, anxiety, and sleep disorders among students. The research employed a quantitative, correlational design, with 109 students from Institut Agama Islam Negeri Kerinci, Indonesia, as research participants. Data were collected using instruments such as the Sleep Quality Scale (Cronbach's alpha 0.969), Academic Anxiety Scale (Cronbach's alpha 0.956), and Academic Stress Scale (Cronbach's alpha 0.980). The data were analyzed using descriptive statistics, as well as simple and multiple regression tests. The results indicate a correlation between the level of academic stress and academic anxiety and the incidence of sleep disorders in college students. In summary, higher levels of academic stress and anxiety increase the likelihood of individuals experiencing sleep disorders. It is expected that future research will expand the sample population to allow for more generalizable results for the student population.